Photovoltaic electroforming screen printing plate and preparation forming process thereof
By drawing electroformed pattern areas on a substrate using an electroforming process, and combining specific electroforming solutions and additives, the problems of complex screen printing plate making, poor straightness, and low lifespan in photovoltaic cells have been solved, achieving efficient and low-cost screen preparation.
Patent Information
- Application Number
- CN202411803609.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing screen printing processes for photovoltaic cells are complex, have poor screen straightness, are difficult to set up film, have long production cycles, short service life, high costs, and poor wear resistance.
Electroforming is used to draw electroformed patterns on a substrate. Electroforming is used to form a single piece, which simplifies the multiple baking, exposure, development and degreasing processes of photosensitive material coating, sealing and edge sealing. Electroforming solution with specific components and additives such as aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate are used to optimize the bonding force and stress between the coating and the substrate mold, thereby improving the strength and toughness of the electroformed screen.
It improves the straightness and wear resistance of the screen printing plate, simplifies the plate making process, extends the service life, reduces costs, and increases the yield and production efficiency.
Smart Images

Figure CN119307987A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of photovoltaic technology, and more specifically, to a photovoltaic electroforming screen and a preparation and molding process thereof. Background Art
[0002] The existing screens for printing solar crystalline silicon cells need to be degreased, drawn, and degreased multiple times to press the polyimide film onto the metal mesh. After the hot pressing process, a layer of photosensitive material needs to be applied to prevent slurry seepage between the polyimide film and the polyethylene film. The graphic parts are all made of diazo-type photosensitive materials. The plate-making process is complicated and requires two pressings, two exposures, and development, and multiple baking and degreasing processes to form the graphics and achieve the effect of printing. The plate-making cycle is too long, and the plate-making process has very strict requirements on the cleanliness, temperature, and humidity of the environment. The mesh is formed by a metal wire weaving process, resulting in poor straightness of the mesh, difficulty in film typesetting, easy cracking at the interface, and slurry leakage during printing, resulting in low yields. The cost of screen production is extremely high, and the screen produced is not wear-resistant and has a short service life. Summary of the invention
[0003] In view of the problems that the existing platemaking process is complicated and numerous, the mesh straightness is poor, the film layout is difficult, the platemaking cycle is long, and the service life is short, the present application provides a photovoltaic electroforming screen and its preparation and molding process.
[0004] In the first aspect, the present application provides a process for preparing and forming a photovoltaic electroforming screen, which adopts the following technical solution: A preparation and molding process for a photovoltaic electroforming screen, comprising the following steps: S1: substrate mold pattern: drawing an electroforming pattern area on a substrate; filling the border design area with warp and weft lines, with a mesh count of 800-1200 and a line diameter of 16-24 μm; S2: Preparation of electroforming solution: 98-117 g / L of nickel sulfate, 21-27 g / L of cobalt sulfate, 18-21 g / L of nickel chloride, 23-27 g / L of boric acid, 7-17 g / L of sodium gluconate, 1-3 g / L of sodium dodecyl sulfate, and 25-31 ml / L of additives; wherein the additives include aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate; S3: placing the substrate in an electroforming liquid, electroforming the substrate into an integrated unit, and performing a demolding treatment to obtain a photovoltaic electroforming screen.
[0005] By adopting the above technical scheme, the present application adopts the electroforming method, by drawing the electroforming graphic area on the substrate mold, and electroforming one-piece molding, and demolding directly to obtain the photovoltaic electroforming screen. By pre-making a mold with a pattern, the electroforming molding optimizes the drawing process to draw metal wires, so as to avoid the poor straightness of the mesh after being made into a photovoltaic printing screen and the difficulty of typesetting. At the same time, the one-piece molding method simplifies the photosensitive material coating edge sealing multiple baking, exposure development and degreasing processes. Avoid the problems of poor straightness of the mesh, difficulty in film typesetting, long plate making cycle and low screen life. Secondly, by adjusting the preparation components of the electroforming solution and selecting additives, the strength is higher and the thermal conductivity is better. By adjusting the composition of the plating solution, the bonding force between the coating and the substrate mold is good, the stress is small, the graphic electroforming is more complete and defect-free, and the service life of the screen is extended. The addition of aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate further increases the strength and toughness of the electroformed mesh. The active sites at the edge of the β-cyclodextrin cavity interact with aluminum nitride, and the aminosulfonate increases the compatibility of the additive with the components in the electroforming liquid. This makes the electroformed mesh high in strength and free of defects such as cracks, peeling, and bubbling on the coating surface. This allows the electroformed mesh to better withstand scraper friction, which increases its service life and prevents edge cracking.
[0006] In a specific embodiment, the mass ratio of the aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate is (5-8):1:(9-16).
[0007] By adopting the above technical scheme, aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate are mixed and used within a certain proportion range to improve the mechanical properties of the electroforming screen. Through the interaction reaction between cyclodextrin and sodium aminosulfonate, a structural molecular form of multiple cyclodextrins with anionic sulfonic acid groups that are cross-linked with each other is formed, so that it can be better combined with other inorganic salts in the electroforming liquid, enhance the electroplating effect of the electroforming liquid, and make the surface smooth without crack defects. Too much aluminum nitride will make the material harder and less tough, affecting the service life; the β-cyclodextrin molecular structure has the characteristics of rigidity, symmetry and modifiability, which can increase the stability of the electroforming liquid. Too little content will affect the stability and durability of the electroforming mesh.
[0008] In a specific embodiment, the electroforming conditions are pH 3.5-3.7, current density 4-7A / dm 2 , temperature 46-62℃, electroplating time is 3-7h.
[0009] By adopting the above technical solution and setting the electroforming process conditions, the electroforming screen has a high yield rate, good wear resistance and increased service life.
[0010] In a specific possible implementation scheme, the photovoltaic electroforming screen includes a central electroforming pattern, a buffer area pattern, a solid area and a border design area from the center to the outer circle.
[0011] By adopting the above technical solution, the photovoltaic electroforming screen can effectively improve the straightness of the screen and not easily cause steel wire deformation; on the other hand, it can save multiple production processes and improve production efficiency; secondly, the solid area can effectively improve the edge leakage problem, improve the overall strength of the mesh, resist scraper friction, thereby preventing the mesh from cracking and increasing the life of the screen; the buffer area can facilitate film layout.
[0012] In a specific possible implementation manner, the central electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:(1-3).
[0013] In a specific implementation manner, the buffer region pattern is a regular hexagonal grid, the diameter of the regular hexagon is 280-420 mesh, and the wire diameter is 8-12 μm.
[0014] By adopting the above technical solution, the buffer area is designed with regular hexagonal meshes, which has a strong stability effect and is easier to typeset. By controlling the process-related parameters, the final form of the screen and the three-dimensional shape of the grid can be effectively controlled, further improving the typesetting efficiency and increasing the printing service life.
[0015] In a specific embodiment, the thickness of the solid region is 17-21 μm.
[0016] The electroforming graphic area does not contact the intersection points of longitude and latitude lines in adjacent graphic areas during the drawing process.
[0017] By adopting the above technical solution, typesetting is made easier and the electroformed mesh has better wear resistance, which prevents overlapping between graphic areas, reduces the difficulty of graphic design, reduces the time for typesetting during graphic design, and improves printing efficiency.
[0018] Photovoltaic electroforming screen prepared by the preparation and molding process of photovoltaic electroforming screen.
[0019] In summary, this application has the following beneficial effects: 1. The present application adopts the electroforming method, by drawing the electroforming graphic area on the substrate mold, and performing electroforming integrated molding, and then demolding to directly obtain the photovoltaic electroforming screen. By pre-making a mold with a pattern, the electroforming molding optimizes the drawing process to draw metal wires, thereby avoiding the poor straightness of the mesh after it is made into a photovoltaic printing screen and the difficulty in typesetting. At the same time, the one-piece molding method simplifies the photosensitive material coating, edge sealing, multiple baking, exposure, development and degreasing processes. Avoid the problems of poor straightness of the mesh, difficulty in film typesetting, long plate making cycle and short screen life. Secondly, by adjusting the preparation components of the electroforming solution and selecting additives, the strength is higher and the thermal conductivity is better. By adjusting the composition of the plating solution, the coating has good bonding with the substrate mold, the stress is small, the graphic electroforming is more complete and defect-free, and the service life of the screen is extended. The addition of aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate further increases the strength and toughness of the electroformed mesh. The active sites at the edge of the β-cyclodextrin cavity interact with aluminum nitride, and the aminosulfonate increases the compatibility of the additive with the components in the electroforming liquid. This makes the electroformed mesh high in strength and free of defects such as cracks, peeling, and bubbling on the coating surface. This allows the electroformed mesh to better withstand scraper friction, which increases its service life and prevents edge cracking.
[0020] 2. The mechanical properties of the electroforming screen are improved by mixing aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate in a certain proportion. The interaction between cyclodextrin and sodium aminosulfonate forms a structural molecule in which multiple cyclodextrins with anionic sulfonic acid groups are cross-linked, so that it can be better combined with other inorganic salts in the electroforming liquid, enhance the electroplating effect of the electroforming liquid, and make the surface smooth without crack defects. Too much aluminum nitride will make the material harder and less tough, affecting its service life. The molecular structure of β-cyclodextrin has the characteristics of rigidity, symmetry and modifiability, which increases the stability of the electroforming liquid. Too little will affect the stability and durability of the electroforming mesh.
[0021] 3. On the one hand, photovoltaic electroforming screen can effectively improve the straightness of the screen and is not easy to cause steel wire deformation; on the other hand, it can save multiple production processes and improve production efficiency; secondly, the solid area can effectively improve the edge leakage problem, improve the overall strength of the mesh, resist scraper friction, thereby preventing the mesh from cracking and increasing the life of the screen; the buffer area can facilitate film layout. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the overall structure of the photovoltaic electroforming screen provided in Example 1 of the present application.
[0023] Explanation of the accompanying reference numerals: 1. Center electroforming pattern; 2. Buffer area pattern; 3. Solid area; 4. Border design area. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with embodiments.
[0025] Some raw materials used in the preparation examples and embodiments: Aluminum nitride (specification: 10 nm): purchased from Nangong Jiuxin New Material Technology Co., Ltd.
[0026] The raw materials used in the examples and comparative examples that are not otherwise specified are all conventional products that can be purchased from the market.
[0027] Example 1: Figure 1 As shown, a photovoltaic electroforming screen includes, from the center to the outer circle, a central electroforming pattern 1, a buffer area pattern 2, a solid area 3 and a frame design area 4; wherein the central electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the buffer area pattern is a regular hexagonal grid, the diameter of the regular hexagon is 280 mesh, and the wire diameter is 8μm; the thickness of the solid area is 17μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additives are aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate, and the mass ratio of aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate is 5:1:16. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0028] Embodiment 2: A photovoltaic electroforming screen, comprising, from the center to the outer circle, a center electroforming pattern 1, a buffer area pattern 2, a solid area 3 and a frame design area 4; wherein the center electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:3; the buffer area pattern is a regular hexagonal grid, the diameter of the regular hexagon is 420 mesh, and the wire diameter is 12 μm; the thickness of the solid area is 21 μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 800 mesh, and the wire diameter is 24μm. S2: Preparation of electroforming liquid: 98g / L nickel sulfate, 27g / L cobalt sulfate, 18g / L nickel chloride, 27g / l boric acid, 7g / L sodium gluconate, 3g / L sodium dodecyl sulfate, and 25ml / L additives are mixed, and stirred at 82°C for 1h to obtain an electroforming liquid; wherein the additives are aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate, and the mass ratio of aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate is 8:1:9. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.7 and the current density to 4A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0029] Embodiment 3: A photovoltaic electroforming screen, comprising, from the center to the outer circle, a center electroforming pattern 1, a buffer area pattern 2, a solid area 3 and a frame design area 4; wherein the center electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the buffer area pattern is a regular hexagonal grid, the diameter of the regular hexagon is 280 mesh, and the wire diameter is 8 μm; the thickness of the solid area is 17 μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additives are aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate, and the mass ratio of aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate is 11:1:9. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0030] Embodiment 4: A photovoltaic electroforming screen, comprising, from the center to the outer circle, a center electroforming pattern 1, a buffer area pattern 2, a solid area 3 and a frame design area 4; wherein the center electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the buffer area pattern is a regular hexagonal grid, the diameter of the regular hexagon is 280 mesh, and the wire diameter is 8 μm; the thickness of the solid area is 17 μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additives are aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate, and the mass ratio of aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate is 5.5:0.5:16. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0031] Embodiment 5: A photovoltaic electroforming screen, comprising, from the center to the outer circle, a center electroforming pattern 1, a buffer area pattern 2, a solid area 3 and a frame design area 4, wherein the center electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the buffer area pattern is a regular hexagonal grid, the diameter of the regular hexagon is 280 mesh, and the wire diameter is 8 μm; the thickness of the solid area is 10 μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additives are aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate, and the mass ratio of aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate is 5:1:16. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0032] Embodiment 6: A photovoltaic electroforming screen, comprising, from the center to the outer circle, a center electroforming pattern 1, a buffer area pattern 2, a solid area 3 and a frame design area 4, wherein the center electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the buffer area pattern is a square grid, the diameter of the square is 280 mesh, and the wire diameter is 8 μm; the thickness of the solid area is 17 μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additives are aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate, and the mass ratio of aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate is 5:1:16. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0033] Embodiment 7: A photovoltaic electroforming screen, comprising, from the center to the outer circle, a central electroforming pattern 1, a solid area 3 and a frame design area 4; wherein the central electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the thickness of the solid area is 17 μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additives are aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate, and the mass ratio of aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate is 5:1:16. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0034] Embodiment 8: A photovoltaic electroforming screen, comprising, from the center to the outer circle, a central electroforming pattern 1, a buffer area pattern 2 and a frame design area 4; wherein the central electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the buffer area pattern is a regular hexagonal grid, and the diameter of the regular hexagon is 280 meshes and the wire diameter is 8 μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additives are aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate, and the mass ratio of aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate is 5:1:16. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0035] Comparative Example Comparative Example 1 A photovoltaic electroforming screen, comprising, from the center to the outer circle, a central electroforming pattern 1, a buffer area pattern 2, a solid area 3 and a frame design area 4; wherein the central electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the buffer area pattern is a regular hexagonal grid, the diameter of the regular hexagon is 280 mesh, and the wire diameter is 8μm; the thickness of the solid area is 17μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additives are aluminum nitride powder and sodium aminosulfonate, and the mass ratio of aluminum nitride powder to sodium aminosulfonate is 5:17. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0036] Comparative Example 2 A photovoltaic electroforming screen, comprising, from the center to the outer circle, a central electroforming pattern 1, a buffer area pattern 2, a solid area 3 and a frame design area 4; wherein the central electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the buffer area pattern is a regular hexagonal grid, the diameter of the regular hexagon is 280 mesh, and the wire diameter is 8μm; the thickness of the solid area is 17μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additives are β-cyclodextrin and sodium aminosulfonate, and the mass ratio of β-cyclodextrin to sodium aminosulfonate is 1:21. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0037] Comparative Example 3 A photovoltaic electroforming screen, comprising, from the center to the outer circle, a central electroforming pattern 1, a buffer area pattern 2, a solid area 3 and a frame design area 4; wherein the central electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the buffer area pattern is a regular hexagonal grid, the diameter of the regular hexagon is 280 mesh, and the wire diameter is 8μm; the thickness of the solid area is 17μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additives are aluminum nitride powder and β-cyclodextrin, and the mass ratio of aluminum nitride powder to β-cyclodextrin is 21:1. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0038] Comparative Example 4 A photovoltaic electroforming screen, comprising, from the center to the outer circle, a central electroforming pattern 1, a buffer area pattern 2, a solid area 3 and a frame design area 4; wherein the central electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the buffer area pattern is a regular hexagonal grid, the diameter of the regular hexagon is 280 mesh, and the wire diameter is 8μm; the thickness of the solid area is 17μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additive is aluminum nitride powder. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0039] Comparative Example 5 A photovoltaic electroforming screen, comprising, from the center to the outer circle, a central electroforming pattern 1, a buffer area pattern 2, a solid area 3 and a frame design area 4; wherein the central electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the buffer area pattern is a regular hexagonal grid, the diameter of the regular hexagon is 280 mesh, and the wire diameter is 8μm; the thickness of the solid area is 17μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additive is β-cyclodextrin. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0040] Comparative Example 6 A photovoltaic electroforming screen, comprising, from the center to the outer circle, a central electroforming pattern 1, a buffer area pattern 2, a solid area 3 and a frame design area 4; wherein the central electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:1; the buffer area pattern is a regular hexagonal grid, the diameter of the regular hexagon is 280 mesh, and the wire diameter is 8μm; the thickness of the solid area is 17μm; A preparation and molding process for a photovoltaic electroforming screen, S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, the mesh size is 1200 mesh, and the wire diameter is 16μm. S2: Preparation of electroforming liquid: 117g / L nickel sulfate, 21g / L cobalt sulfate, 21g / L nickel chloride, 23g / l boric acid, 17g / L sodium gluconate, 1g / L sodium dodecyl sulfate, and 31ml / L additives are mixed, and stirred at 70°C for 2h to obtain an electroforming liquid; wherein the additive is sodium aminosulfonate. S3: Place the substrate in the electroforming liquid and adjust the pH value to 3.5 and the current density to 7A / dm 2 , temperature 46 ℃, after electroplating for 3h, the photovoltaic electroforming screen was obtained by demolding.
[0041] The photovoltaic electroforming screen prepared in the embodiment has high wear resistance, high straightness, easy film layout, stable and firm interface, and meets the needs of the photovoltaic cell industry. The embodiment meets the photovoltaic industry screen requirements with a yield rate of over 90%, no side wall cracking after molding, simple preparation, low cost, and good mechanical properties of the electroforming screen. The photovoltaic electroforming screen prepared in Examples 1-2 has better electroplating effect of the electroforming liquid, a smooth surface without crack defects, and better stability and durability of the electroformed mesh. The yield rate of Examples 1-2 exceeds 95%. By comparing Example 1 and Example 3-4, it can be seen that by mixing aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate in a certain proportion range, the mechanical properties of the electroforming screen are improved, and the interaction reaction between cyclodextrin and sodium aminosulfonate forms a structural molecular form in which multiple cyclodextrins with anionic sulfonic acid groups are cross-linked, so that it can be better combined with other inorganic salts in the electroforming liquid, enhance the electroplating effect of the electroforming liquid, and make the surface smooth and free of crack defects. In Example 3, too much aluminum nitride will make the material harder and less tough, affecting the service life, and the long-term use rate is slightly lower than that of Examples 1-2. In Example 4, the β-cyclodextrin molecular structure has the characteristics of rigidity, symmetry and modifiability, which increases the stability of the electroforming liquid. Too little content will affect the stability and durability of the electroforming mesh.
[0042] Compared with the screens prepared in Example 1 and Example 5, due to the insufficient thickness of the solid area, some slurry leakage occurred during use, resulting in defective products, and the yield rate was slightly lower than that of Example 1-2; Compared with the screens prepared in Example 1 and Example 6, some grids were squeezed and deformed during layout, resulting in a yield rate of 90%. In Example 7 and Example 8, the film strength was insufficient or cracked during layout, resulting in defective products, and the yield rate was slightly lower than that of Example 6.
[0043] The photovoltaic electroforming screen prepared in the comparative example is simple to prepare and low in cost, but the yield rate reaches 70%. However, the long-term performance is not high, the mesh cracks, and the edge leakage is serious, and the service life is worse than that of the embodiment.
[0044] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A process for preparing and forming a photovoltaic electroforming screen, characterized in that: The following steps are included: S1: Substrate mold graphics: by drawing the electroforming graphic area on the substrate; the border design area is filled with warp and weft lines, with a mesh count of 800-1200 and a wire diameter of 16-24μm; S2: Preparation of electroforming solution: 98-117g / L nickel sulfate, 21-27g / L cobalt sulfate, 18-21g / L nickel chloride, 23-27g / L boric acid, 7-17g / L sodium gluconate, 1-3g / L sodium dodecyl sulfate, and 25-31ml / L additives; wherein, The additives include aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate; S3: placing the substrate in an electroforming liquid, electroforming the substrate into an integrated unit, and performing a demolding treatment to obtain a photovoltaic electroforming screen.
2. The process for preparing and forming a photovoltaic electroforming screen according to claim 1, characterized in that: The mass ratio of the aluminum nitride powder, β-cyclodextrin and sodium aminosulfonate is (5-8):1:(9-16).
3. The process for preparing and forming a photovoltaic electroforming screen according to claim 1, characterized in that: The electroforming conditions are pH 3.5-3.7, current density 4-7A / dm 2 , temperature 46-62℃, electroplating time is 3-7h.
4. The process for preparing and forming a photovoltaic electroforming screen according to claim 1, characterized in that: The photovoltaic electroforming screen comprises, from the center to the outer circle, a central electroforming pattern (1), a buffer area pattern (2), a solid area (3) and a frame design area (4).
5. The process for preparing and forming a photovoltaic electroforming screen according to claim 4, characterized in that: The central electroforming pattern is a rectangular grid, and the length ratio of the long side to the short side is 1:(1-3).
6. The process for preparing and forming a photovoltaic electroforming screen according to claim 4, characterized in that: The buffer area pattern is a regular hexagonal grid, the diameter of the regular hexagon is 280-420 meshes, and the wire diameter is 8-12 μm.
7. The process for preparing and forming a photovoltaic electroforming screen according to claim 4, characterized in that: The thickness of the solid area (3) is 17-21 μm.
8. The process for preparing and forming a photovoltaic electroforming screen according to claim 1, characterized in that: The electroforming graphic area does not contact the intersection points of longitude and latitude lines in adjacent graphic areas during the drawing process.
9. A photovoltaic electroforming screen prepared by the photovoltaic electroforming screen preparation and molding process according to any one of claims 1 to 8.
Citation Information
Patent Citations
High-precision metal membrane composite nickel net and electroforming manufacturing method
CN105734617A
Nanometer aluminum nitride composite electroplating solution and electroplating method
CN107460527A
Electroforming solution, electroforming method and application of electroforming solution to photographic fixing film of laser printer
CN114775003A
Screen printing plate and electroforming method thereof
CN116103705A
Double layer nickel metal composite electromoulding printing screen
CN201020914Y
Cited By
High-strength full-opening nickel alloy screen printing plate and processing technology thereof
CN120902420A
High-strength full-opening nickel alloy screen printing plate
CN224510641U